Efectos in vitro e in vivo de la pulpa de mango (Mangifera indica cv. Azúcar) en la carcinogénesis de colon (2014)
ABSTRACT: Mango pulp contains ascorbic acid, carotenoids, polyphenols, terpenoids and fiber which are healthy and could protect against colon cancer. The aim of this study was to evaluate the antiproliferative and preventive capacity of an aqueous extract of Mangifera indica cv. Azúcar on a human colon adenocarcinoma cell line (SW480) and in a rodent model of colorectal cancer, respectively. The content of total phenolics, flavonoids and carotenoids were also analyzed in the extract. SW480 cell growth was inhibited in a dose and time dependent manner by 22.3% after a 72h exposure to the extract (200 μg/ mL). Colon carcinogenesis was initiated in Balb/c mice by two intra-peritoneal injections of azoxymethane (AOM) at the third and fourth week of giving mango in drinking water (0.3%, 0.6%, 1.25%). After 10 weeks of treatment, in the colon of mice receiving 0.3% mango, aberrant crypt foci formation was inhibited more than 60% (p=0,05) and the inhibition was dose-dependent when compared with controls receiving water. These results show that mango pulp, a natural food, non toxic, part of human being diet, contains bioactive compounds able to reduce growth of tumor cells and to prevent the appearance of precancerous lesions in colon during carcinogenesis initiation.